East Coast Encounter - Chandler, L; Waldron, John (2014)
The East Coast Encounter (ECE) is a multi-arts initiative involving significant Australian Indigenous and non-Indigenous artists, writers and songwriters to re-imagine the encounter by Lt. James Cook and his crew with Aboriginal people in 1770. Cook’s voyage along the Australian east coast has become central to national historical narratives. The exhibition is innovative in seeking to re-envisage this seminal journey by imaginatively exploring moments of contact between two world views during these encounters. In addressing the exhibition’s theme, the artists will produce work which is informed by several key sites where Cook and his crew engaged with Indigenous people: Botany Bay, K’gari/Fraser Island, Town of 1770, Palm Island and Cooktown as well as the highly symbolic site of Possession Island. Works will explore topics such as literal and metaphorical encounter, reconciliation, differing ways of seeing and knowing, journeys and forms of mapping, nature and culture, and views of country. The exhibition features work by prominent and emerging artists, working across a range of art forms, whose creative practice explores aspects of country and culture and who are recognised as distinctive story-tellers. Additionally, the selected artists broadly represent the key encounter language group nations and regions. Exhibition works will incorporate a range of media including painting, photography, three-dimensional works and installation. These will be enhanced and juxtaposed by a small selection of historical artefacts and documents. Another component of ECE will be the inclusion of historical and contemporary material and performances by leading singer songwriter/poets. A short documentary on DVD, created by Jeff McMullen and Adric Watson, will further enrich the exhibition by giving additional voice to the artists, capturing their own encounters with significant sites and traditional owners, and showing how their varying viewpoints sit together. East Coast Encounter will also be informed by dialogue, exchange and cultural material from the many Aboriginal nations along coastal NSW and Queensland. Connection with some communities has been undertaken, with appropriate protocols, by participating artists and curators. These dialogues will be expanded by an indigenous researcher. It is anticipated that there may be oral histories and other material held within the communities that can inform the project, including the publications, and contribute to the ethos of balance and access that underpins the exhibition. Visiting various sites has been a profound and moving experience for many of the participants. The resulting engagements with traditional owners, communities and places connected with the historical encounter have been central to the development of East Coast Encounter and inform the final works. Exhibition: Australian National Maritime Museum, Sydney, 9 May - 24 August 2014